Evidence of the content validity, acceptability, and feasibility of a new Patient-Reported Impact of Dermatological Diseases measure - Pattinson, Rachael; Trialonis-Suthakharan, Nirohshah; Hewitt, Rachael M.; Valencia López, Maria José; Tahmasebi Gandomkari, Nasim; Austin, Jennifer; FitzGerald, Allison; Courtier, Nick; Augustin, Matthias; Bundy, Chris (Frontiers in Medicine, 2023)
Background The Global Research on the Impact of Dermatological Diseases (GRIDD) team is developing the new Patient-Reported Impact of Dermatological Diseases (PRIDD) measure of the impact of dermatological conditions on the patient’s life, in partnership with patients. To develop PRIDD, we conducted a systematic review, followed by a qualitative interview study with 68 patients worldwide and subsequently a global Delphi survey of 1,154 patients to ensure PRIDD items were meaningful and important to patients. Objective To pilot test PRIDD with patients with dermatological conditions, focusing on its content validity (comprehensiveness, comprehensibility, and relevance), acceptability, and feasibility. Methods We conducted a theory-led qualitative study using the Three-Step Test-Interview method of cognitive interviewing. Three rounds of semi-structured interviews were conducted online. Adults (≥ 18 years) living with a dermatological condition and who spoke English sufficiently to take part in the interview were recruited through the International Alliance of Dermatology Patient Organizations’ (GlobalSkin) global membership network. The topic guide met the gold-standard COSMIN (Consensus-based Standards for the Selection of Health Measurement Instruments) standards for cognitive interviewing. Analysis followed the thematic analytical model of cognitive interviewing. Results Twelve people (58% male) representing six dermatological conditions from four countries participated. Overall, patients found PRIDD to be comprehensible, comprehensive, relevant, acceptable, and feasible. Participants were able to discern the conceptual framework domains from the items. Feedback resulted in: the recall period being extended from 1 week to 1 month; removal of the ‘not relevant’ response option; and changes to the instructions and item ordering and wording to improve clarity and increase respondents’ confidence in their ability to respond. These evidence-based adjustments resulted in a 26-item version of PRIDD. Conclusion This study met the gold-standard COSMIN criteria for the pilot testing of health measurement instruments. The data triangulated our previous findings, in particular the conceptual framework of impact. Our findings illuminate how patients understand and respond to PRIDD and other patient-reported measurement instruments. The results of comprehensibility, comprehensiveness, relevance, acceptability, and feasibility of PRIDD provide evidence of content validity from the target population. The next step in the development and validation of PRIDD is psychometric testing.